2023
DOI: 10.1063/5.0138939
|View full text |Cite
|
Sign up to set email alerts
|

N-polar GaN/AlGaN/AlN high electron mobility transistors on single-crystal bulk AlN substrates

Abstract: Recent observation of high density polarization-induced two-dimensional electron gases in ultra-thin N-polar GaN layers grown on single-crystal AlN has enabled the development of N-polar high electron mobility transistors (HEMTs) on AlN. Such devices will take advantage of thermal and power handling capabilities of AlN, while simultaneously benefitting from the merits of N-polar structures, such as a strong back barrier. We report the experimental demonstration of N-polar GaN/AlGaN/AlN HEMTs on single-crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Ga 2 O 3 possesses five polymorphs, specifically α, β, γ, δ, and ε. Among these, the ε-phase is noted for its remarkable polarization property, which is an order of magnitude greater than GaN, a semiconductor material typically employed in high electron mobility transistors (HEMTs). , The findings on polarization of ε-phase Ga 2 O 3 have piqued the interest of numerous researchers that are exploring the possibilities of ε-Ga 2 O 3 based devices. Chen et al have reported on the polarization switching properties of κ-Ga 2 O 3 (where κ and ε denote the same phase of Ga 2 O 3 ) in κ-Ga 2 O 3 /GaN heterostructure, revealing a remanent polarization of approximately 2.7 μC/cm 2 . Wang et al have indicated that the interface of ε-Ga 2 O 3 / m -GaN ( m -AlN) could achieve a high two-dimensional electron gas (2DEG) density of 10 14 cm –2 .…”
Section: Introductionmentioning
confidence: 99%
“…Ga 2 O 3 possesses five polymorphs, specifically α, β, γ, δ, and ε. Among these, the ε-phase is noted for its remarkable polarization property, which is an order of magnitude greater than GaN, a semiconductor material typically employed in high electron mobility transistors (HEMTs). , The findings on polarization of ε-phase Ga 2 O 3 have piqued the interest of numerous researchers that are exploring the possibilities of ε-Ga 2 O 3 based devices. Chen et al have reported on the polarization switching properties of κ-Ga 2 O 3 (where κ and ε denote the same phase of Ga 2 O 3 ) in κ-Ga 2 O 3 /GaN heterostructure, revealing a remanent polarization of approximately 2.7 μC/cm 2 . Wang et al have indicated that the interface of ε-Ga 2 O 3 / m -GaN ( m -AlN) could achieve a high two-dimensional electron gas (2DEG) density of 10 14 cm –2 .…”
Section: Introductionmentioning
confidence: 99%
“…As a direct bandgap semiconductor with a wide bandwidth of 6.2 eV and a high breakdown field strength (>1.2 × 10 6 V·cm –1 ), it has a large thermal conductivity (285 W·m –1 ·K –1 at 300 K), and the lattice parameters and the thermal expansion coefficient of AlN well match to GaN or Al x Ga (1– x ) N. , High-quality single-crystal AlN substrates are expected to greatly reduce defect densities in overgrown device structures, improving the performance and lifetime of devices. Due to these superior properties, there are many applications of AlN substrate that have been implemented or are being explored, including deep-ultraviolet photoelectric devices , and electronics operating at high-power, high-frequency, and high-temperature environments. , …”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Recently, an N-polar GaN/AlGaN/AlN HEMT was demonstrated using MBE. 21) Metal-organic vapor-phase epitaxy (MOVPE) is a promising growth technique for the mass production of nitride semiconductors. However, the fabrication of N-polar-surface GaN/AlN structures using MOVPE is problematic.…”
Section: Introductionmentioning
confidence: 99%